Temporal Trends of Influenza A (H1N1) Virus Seroprevalence following 2009 Pandemic Wave in Guangdong, China: Three Cross-Sectional Serology Surveys - Yang, Fen; He, Jianfeng; Zhong, Haojie; Ke, Changwen; Zhang, Xin; Hong, Teng; Ni, Hanzhong; Lin, Jinyan (PLOS ONE, 2012)
Background To evaluate the temporal trends of seroprevalence to pH1N1 among the Guangdong population following 2009 H1N1 pandemic wave, we conducted three cross-sectional serology surveys in 2010. Methodology/Principal Findings Three surveys were carried out consecutively in 2010 from January 8 to January 24, from March 15 to April 10 and from August 23 to September 4. Sample populations comprising of 4725, 4727, and 4721 subjects respectively were randomly selected for study in these three surveys. The level of antibodies against pH1N1 was evaluated by hemagglutination inhibition assay. In survey 1, the seroprevalence of pH1N1 among all the subjects is 25.1%, declining to 18.4% in survey 2 and increasing to 21.4% in survey 3. Among vaccinated subjects, the seroprevalence was 49.0%, 53.0%, and 49.4% in the three consecutive surveys, showing no significant differences. In contrast, among non-vaccinated subjects, the seroprevalence declined significantly from 22.8% (survey 1) to 14.3% (survey 2) and subsequently increased to 18.1% (survey 3). The multivariate logistic regression analysis revealed that seroprevalence to pH1N1 in non-vaccinated individuals correlated with the investigated order of the surveys, age, and region (all P<0.05). However, it was not correlated with gender (P = 0.650), seasonal influenza vaccination history (P = 0.402) and symptoms (P = 0.074). Conclusions/Significance In Guangdong, the seroprevalance to pH1N1 decreased initially and then rebounded modestly during the first 9 months following the 2009 pandemic wave. Our results suggest that the prevalence of pH1N1 is still correlated with age and population density during the post-pandemic period. An early end to the free pH1N1 vaccination program might be another important reason for the slight rebound in seroprevalance. Our study findings can help the Guangdong authorities to make evidence-based decisions about a long-term vaccination strategy and boost immunity in specific population groups (such as children and people living in the capital-city) to prevent further transmission in the future.